2021
DOI: 10.4250/jcvi.2020.0117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Updated 2016 ASE/EACVI VIS-À-VIS 2009 ASE Recommendation on the Prevalence of Diastolic Dysfunction and LV Filling Pressures in Patients with Preserved Ejection Fraction

Abstract: BACKGROUND: Assessment of diastolic dysfunction (DD) and left ventricular filling pressures (LVFP) by echocardiography is complex in patients with preserved ejection fraction (EF). The American Society of Echocardiography and the European Association of Cardiovascular Imaging (ASE/EACVI) jointly published recommendations in 2016 to simplify the diagnosis and classification of DD and the assessment of LVFP. We aimed to study the impact of the updated 2016 ASE/EACVI guidelines vis-à-vis the 2009 ASE recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…The lower prevalence of LV diastolic dysfunction in our study vs. previous ones is mainly due to the change of the echocardiographic criteria used to assess LV diastolic function. Similar discrepancy has been detected in the general population [11–14]. Indeed, we found that the prevalence of LV diastolic dysfunction by adopting the 2016 ASE/ESCVI guidelines resulted significantly lower than the prevalence detected using the 2009 ASE guidelines (22.7% vs. 62.1%, respectively) and allowed us to identify and quantify the group of the indeterminate pattern (45.7%).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The lower prevalence of LV diastolic dysfunction in our study vs. previous ones is mainly due to the change of the echocardiographic criteria used to assess LV diastolic function. Similar discrepancy has been detected in the general population [11–14]. Indeed, we found that the prevalence of LV diastolic dysfunction by adopting the 2016 ASE/ESCVI guidelines resulted significantly lower than the prevalence detected using the 2009 ASE guidelines (22.7% vs. 62.1%, respectively) and allowed us to identify and quantify the group of the indeterminate pattern (45.7%).…”
Section: Discussionsupporting
confidence: 79%
“…This parameter, being less dependent on volume status, is now considered as the most reliable index of diastolic dysfunction at variance with other echocardiographic parameters (e.g. left atrial dilation) [11,36]. This assumption is supported by a previous experimental study in unilateral nephrectomized rats revealing that LV diastolic abnormalities develop prior to the occurrence of changes in eGFR, BP, fluid expansion, and aldosterone activation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation